2014
DOI: 10.1038/ncomms5477
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliation of layered double hydroxides for enhanced oxygen evolution catalysis

Abstract: The oxygen evolution reaction is a key reaction in water splitting. The common approach in the development of oxygen evolution catalysts is to search for catalytic materials with new and optimized chemical compositions and structures. Here we report an orthogonal approach to improve the activity of catalysts without alternating their compositions or structures. Specifically, liquid phase exfoliation is applied to enhance the oxygen evolution activity of layered double hydroxides. The exfoliated single-layer na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

67
1,485
8
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 2,080 publications
(1,623 citation statements)
references
References 40 publications
67
1,485
8
4
Order By: Relevance
“…Such result indicated highly efficient electron transfer between the crystalline CoP and the amorphous CoOx nanoclusters. Third, literature reported that amorphous metal oxide sample has higher amount of randomly oriented bonds and higher structural flexibility relative to its crystalline counterpart, which translates to the formation of higher amount of surface unsaturated sites for facile reactant adsorption 9. In such metal phosphide, the highly electronegative P atoms can draw electron from metal atoms and act as proton carrier, thus contributing towards enhanced electrocatalytic activity 10.…”
Section: Resultsmentioning
confidence: 99%
“…Such result indicated highly efficient electron transfer between the crystalline CoP and the amorphous CoOx nanoclusters. Third, literature reported that amorphous metal oxide sample has higher amount of randomly oriented bonds and higher structural flexibility relative to its crystalline counterpart, which translates to the formation of higher amount of surface unsaturated sites for facile reactant adsorption 9. In such metal phosphide, the highly electronegative P atoms can draw electron from metal atoms and act as proton carrier, thus contributing towards enhanced electrocatalytic activity 10.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, transition‐metal (Fe, Co, Ni, Mn, and Mo)‐based catalysts including metal oxides,23, 24, 25, 26, 27, 28, 29, 30 hydroxides,31, 32, 33, 34, 35 phosphides,36, 37, 38, 39, 40, 41, 42 sulfides,43, 44, 45, 46, 47, 48 selenides,49, 50, 51, 52, 53, 54 and nitrides55, 56, 57, 58, 59, 60, 61, 62 have been highlighted as the most promising candidates of OER and HER electrocatalysts. Especially, layered double hydroxides (LDHs)63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85 and their derivatives (metal hydroxides, oxyhydroxides, oxides, bimetal nitrides, phosphides, sulfides, and selenides)86, 87, 88, 89, 90, 91, 92…”
Section: Introductionmentioning
confidence: 99%
“…The oxometallate mainly includes Ca 2 Nb 3 O 10 , Ba 5 Nb 4 O 15 , SnNb 2 O 6 , K 4 Nb 6 O 17 , SrNb 2 O 6 , HNbWO 6 , Bi 2 WO 6 , Bi 2 MoO 6 , and BiVO 4 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43. The hydroxides can be classified as single metal hydroxides (e.g., Ni(OH) 2 ) and layered double hydroxides (LDHs) including CoCo LDHs, NiCo LDHs, NiFe LDHs, Ni 0.75 V 0.25 LDHs, CoMn LDHs, CoFe LDHs, NiCoFe LDHs, ZnAl LDHs, CuCr LDHs, and MgAl LDHs 44, 45, 46, 47, 48, 49, 50, 51, 52, 53. In addition, the MOFs with the tuned metal centers can also serve as effective catalysts, such as NiCo MOFs,54 NiFe‐MOFs 55…”
Section: Synthesis Of Atomically Thin 2d Multinary Photo Electrocatamentioning
confidence: 99%